Icariin attenuates beta-amyloid-induced neurotoxicity by inhibition of tau protein hyperphosphorylation in PC12 cells - Zeng, Ke-Wu; Ko, Hyeonseok; Yang, Hyun Ok; Wang, Xue-Mei (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Alzheimer's disease (AD) is a neurodegenerative disease characterized by the progressive loss of neurons and production of beta-amyloid proteins (A beta). Hyperphosphorylation of tau protein is proposed to be an early event for the evolution of AD, and may play an important role in A beta-induced neurodegeneration. Icariin, a flavonoid compound from the herb Epimedium brevicornum Maxim, exerts a protective effect on learning and memory abilities in A beta(25-35)-induced AD rats. However, the molecular mechanism of icariin-induced neuroprotective effect against tau protein hyperphosphorylation, which is one of the most representative hallmarks in AD, is still unknown. In the present study, we investigated the inhibitory effect of icariin on A beta(25-35)-induced tau protein hyperphosphorylation on PC12 cells. The results showed that treatment with icariin significantly decreased A beta(25-35)-induced cytotoxity and apoptosis rate through inhibiting tau protein hyperphosphorylation at Ser396, Ser404 and Thr205 sites, respectively. Mechanism study showed that icariin could activate PI3K/Akt signaling pathway, resulting in an inhibitory effect on glycogen synthase kinase (GSK)-3 beta, which is an important kinase response for tau protein hyperphosphorylation in the development of AD. These observations indicate that icariin is capable of attenuating A beta(25-35)-induced tau protein hyperphosphorylation and promoting survival of neuronal cells, meanwhile also provide some insights into the potential signaling pathway that is involved. Thus, this study promises a great potential agent for Alzheimer's disease and other tau pathology-related neuronal degenerative diseases. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: GLYCOGEN-SYNTHASE KINASE-3; ALZHEIMERS-DISEASE; OKADAIC ACID; PHOSPHORYLATION; GSK-3-BETA; GLYCOGEN-SYNTHASE-KINASE-3; NEURODEGENERATION; DEGENERATION; APOPTOSIS; PATHWAYS